The Application of Criminal Law in the Digital Age: A Literature Review of Challenges and Opportunities - Johan Alfred Sarades Silalahi (Universitas Pahlawan Tuanku Tambusai, 2023)
The background of this research topic reflects the need to understand the impact of digital technology development on the criminal law system. The digital age has changed the social, economic and cultural landscape, and posed new challenges to traditional criminal law. Therefore, this research aims to analyse the problems and challenges that arise in the application of criminal law in the digital context, as well as investigate the opportunities or solutions that can be adopted to deal with them. This research is qualitative in nature. The techniques used to obtain information involved careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation and inference. The study results show that the challenges and opportunities in the application of criminal law in the digital era are complex and diverse. Advances in information and communication technology have changed the landscape of crime, causing new challenges for criminal law enforcement. However, amidst these challenges, there are opportunities to utilise technology and collaboration to improve the effectiveness of criminal law enforcement. It is important to adopt a holistic and inclusive approach in dealing with these challenges.